Quality Characteristics of Raw and Cooked Spent Hen Pectoralis major Muscle During Chilled Storage: Effect of Tea Catechins - Chueachuaychoo, Atchariya; Wattanachant , Saowakon; Benjakul, Soottawat (International Journal of Poultry Science, 2010)
The effects of different concentrations (0, 100, 150 and 200 mg/kg samples) of antioxidant from Tea Catechins (TC) on oxidative stability of raw and cooked spent hen Pectoralis major muscles during chilled storage were studied. Adding TC could delay the accumulation of oxidation in both meat without any effect on shear force value and yield throughout chilled storage. However, discoloration of meat caused by adding TC was more pronounced in cooked samples than that found in raw meat.